EFEKTIVITAS PENERAPAN MEDIA PEMBELAJARAN KOMIK PADA PEMBELAJARAN GEOGRAFI DI SMA NEGERI 1 SUNGAI KAKAP - Firmanto, Eko; Parijo, Parijo; Sugiarto, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrakThis study was conducted to determine comic as a learning media on students knowledge of geography subjects of X IIS class SMA Negeri 1 Sungai Kakap and to know the effect of comic as a learning media on students' learning interest in geography subjects of X IIS class SMA Negeri 1 Sungai Kakap. The research used an experiment method with quantitative research forms. The population in this study were students of X IIS class SMA Negeri 1 Sungai Kakap 2017/2018 academic year. The researcher used tests and questionnaires with data analysis techniques used Polled Variance t-Test to collect the data. The results showed that the comic had an influence on students knowledge and interest in learning. The results of further tests with effect Size got a high category influence.Â Keywords: Knowledge, Learning Interest, Comic Learning Media